2021
DOI: 10.3390/met11081235
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical Properties, and Galvanic Corrosion of 10CrNi3MoV Fabricated by Wire Arc Additive Manufacturing

Abstract: Wire arc additive manufacturing (WAAM) technology is widely used in the fields of aerospace, shipbuilding, and automobile industry due to the advantages of fast forming speed, high material utilization and low production cost. WAAM is extremely sensitive to parameters, and different processes and materials produce different deposition effects and properties. Therefore, it is of great significance to study the WAAM formability of various materials. Herein, the microstructure, mechanical properties, and galvanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Tian et al [7] discussed the microstructure, mechanical properties, and galvanic corrosion of 10CrNi3MoV fabricated by WAAM. The results revealed that the deposited layer exhibited a hardness range of 221-282 HV 0.2 , a yield strength above 550 MPa, and a tensile strength above 760 MPa.…”
Section: Contributionsmentioning
confidence: 99%
“…Tian et al [7] discussed the microstructure, mechanical properties, and galvanic corrosion of 10CrNi3MoV fabricated by WAAM. The results revealed that the deposited layer exhibited a hardness range of 221-282 HV 0.2 , a yield strength above 550 MPa, and a tensile strength above 760 MPa.…”
Section: Contributionsmentioning
confidence: 99%
“…Austenitic stainless steels also qualify as trouble-free materials, which is proved by Xie et al [9], Yao et al [22] and Wu et al [23]. Roy et al [2] successfully made a part of AISI 410 martensitic stainless steel; similarly, Lervåg et al [10] for superduplex steel and Tain et al [31] for 10CrNi3MoV steel.…”
Section: Introductionmentioning
confidence: 95%